Pengaruh Brand Awareness, Brand Association, Perceived Quality, Brand Image, Brand Loyalty dan Brand Equity Terhadap Repurchase Intention Pada Produk Miniso - Aulia Rizki Nurita; Laurentia Verina Halim Secapramana (ProBisnis : Jurnal Manajemen, 2025)
This research aims to analyze the influence of brand awareness, brand association, perceived quality, brand image, brand loyalty, and brand equity on repurchase intention on miniso products. Data was collected through a survey with 193 respondents from distributing online quitionnaires. Respondents from this study who were domiciled in Indonesia, at least 17 years old, and have purchased Miniso product at least twice within the past year. This research uses a Structural Equation Modelling (SEM) approach. The Analysis of Moments Structures (AMOS) program was used to carry out data analysis. The results of this research show that brand awareness has an insignificant effect on brand equity, brand association has an insignificant effect on brand equity, perceived quality has a positive and significant effect on brand equity, brand image insignificant effect on brand equity, brand loyalty has a positive and significant effect on brand equity, and brand equity has a positive and significant effect on repurchase intention. This study concludes that perceived quality and brand loyalty are the key dimensions supporting brand equity in increasing repurchase intention toward Miniso products.